Biodiversity in plant, grain and nutritional characteristics of sorghum [Sorghum bicolor (L.) Moench] accessions from Ethiopia and South Africa - Gerrano, Abe Shegro (University of the Free State, 2010)
This study was conducted with the objectives of assessing the genetic diversity of sorghum accessions that were obtained from different geographical locations in Ethiopia, as well as South Africa, using phenotypic traits, AFLP markers, minerals, starch and protein. Twenty phenotypic traits were subjected to ANOVA and highly significant differences were observed for all traits among accessions. Some important characteristics were found to be significantly correlated, which could allow for selection of related secondary characteristics to improve primary characteristics. Cluster analysis grouped accessions into five clusters based on similarity. These results would be useful in a breeding programme for selecting sorghum accessions to improve production. Nine qualitative morphological traits were also analysed using the Shannon Weaver diversity index (H’). The results showed that the average H’ was 0.59. The highest polymorphism was recorded for the glume colour (0.84), while the lowest was recorded in panicle compactness and shape (0.31). This indicated that there was wide variability among accessions studied. The cluster analysis for the qualitative traits also identified accessions based on their similarity and differences based on their genetic distances. Hence, visual selection and measurements of the sorghum attributes in field trials could be used to select the desirable traits and improving yield and stability of the accessions in breeding programmes. AFLP analysis showed high genetic similarity of Ethiopian landraces, as well as breeding material from the Ethiopian and South African sorghum breeding programmes, even though the phenotypical characterisation showed high variability. This indicated the possibility that South African and Ethiopian breeding material may have a common ancestry. The morphological, AFLP and combined morphological and AFLP cluster analysis clearly distinguished between all accessions, even though they were genetically similar. Sorghum kernels were used to determine the mineral, starch and protein composition of the sorghum accessions. The ANOVA of the traits revealed highly significant variation among the accessions studied. Furthermore, PCA grouped accessions according to their similarity/differences in the four quadrants which confirmed that there was variation among them for these nutritional traits. Therefore, there would be potential for selecting accessions for specific mineral and protein content for human consumption, and specific starch and amylose content for industrial use. The sugar content of the stalks also indicated the potential to develop dual sorghum cultivars where both the seed and sugar can be produced from the same plants.
Thesis (Ph.D. (Plant Sciences: Plant Breeding))--University of the Free State, 2010
Keywords: Sorghum -- Ethiopia; Sorghum -- South Africa; Sorghum -- Genetics; Germplasm resources, Plant; Phenotypic diversity; Nutritional composition; Genetic diversity; Characterisation; AFLP